Comparing cognitive-behavior therapy and positive psychology to enhance emotional well-being - Pintado, Sheila; Castillo, Marco; Penagos-Corzo, Julio C. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
The effect of adding a cognitive behavioral program to an intervention program in Positive Psychology was. For this purpose, 45 university students were measured by SWLS, PANAS, CES-D, BAI and HADS scales and assigned to one of two groups: a) intervention with positive psychology or b) intervention with more cognitive-behavioral positive psychology. Pre-post comparisons indicate that a Positive Psychology intervention significantly increases life satisfaction and positive affect and significantly decreases negative affect, depressive symptoms and anxiety symptoms (p < .05). Moreover, ANCOVA analysis show that the Cognitive-behavioral intervention does not contributed anything additional to the program of positive psychology in each of the variables measured (p > .05). In short, our findings suggest that it is possible to offer psychological assistance by providing tools from Positive Psychology that promote well-being and psychological health focusing on maximizing strengths within a small period intervention. Keywords: anxiety; depression; positive emotions; wellness; psychological health